Peningkatan Kemampuan Berpikir Kreatif Matematis Siswa SMPN 1 Cikancung Melalui Pendekatan Kontekstual - Mayang Sinta Frestianti; Gagan Aditya Fauzan; M. Diki Fadilah; Risma Amelia (Journal on Education, 2020)
This research was conducted at Cikancung 01 Middle School on class VIII triangle material. This research uses the "Quasi-Experiment" method with the researcher accepting what is the sample with a random class. The research aims to determine the differences in students' mathematical creative thinking abilities between classes that use contextual learning and classes that use normal approaches. This study was applied to 25 students in both the experimental and control classes as a sample with the duration of the study consisting of 6 meetings. Based on the posttest data analysis shows that there are significant differences in mathematical creative thinking abilities where students' mathematical creative thinking abilities with the use of contextual approaches are better than classes with ordinary approaches to learning. This is because the use of contextual approaches provides meaningful learning by seeing, searching, and exploring objects in real life into mathematics learning.